TRANSFORMATION OF EDUCATIONAL COMMUNICATION IN A DIGITALIZED SOCIETY: ANTHROPOLOGICAL ASPECT - Kleshnia, Hanna (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2025)
Digital technologies penetrate all levels of education, driving integrative changes in social communication. Innovations like artificial intelligence, virtual reality, 3D printing, and Big Data profoundly impact modern life, transforming learning methods, communication, and the foundations of personal development and worldview formation. The aim of the article is the philosophical reflection on the transformation of educational communication in a digitalized society. Research methods are general philosophical methods – analysis and synthesis, generalization, structural-functional analysis – as well as anthropological and axiological approaches. These methods enabled the study to demonstrate the transformation of educational communication and its impact on shaping individuals in a digitalized society. Research results. The study of digitalization processes is tied to the historical specifics of modern society and its gradual transformation under various influences. This society demands new educational approaches for rapid adaptation and effective use of digital technologies. However, the drawbacks of digitalization should not be overlooked. In the non-linear development paradigm, knowledge accumulation does not always translate into qualitative growth, as shown in assessments of education quality in the digital age. The anthropological dimension of educational communication reveals how teaching and knowledge transfer are reshaped by the integration of digital technologies. Discussion. A key factor in rebuilding our country is the development of human capital. Researchers L. Drotianko, S. Ordenov, and N. Chenbai highlight the importance of social and humanities disciplines in preparing individuals for today's challenges. These mandatory subjects in higher education significantly contribute to this goal. Scholars in pedagogy, psychology, and philosophy also emphasize maintaining diverse forms of communication in education. Conclusions. Preserving worldview as a key human trait linked to thinking is a critical task for modern education. Digital technologies transform how information is produced, consumed, and how humans interact with machines. However, digitalization also brings challenges, such as socialization issues from changing communication in education. Balancing technological development with ethical, legal, and social considerations is essential for harmonious personal growth